THE RELATIONSHIP BETWEEN TAX AVOIDANCE AND FIRM VALUE, MODERATED BY EXECUTIVE COMPENSATION - Muhamad Safiq; Stevani Phan; Widyahayu Warmmeswara Kusumastati (Jurnal Inovasi Penelitian, 2021)
This research attempts to find out the significant relationship between tax avoidance and firm value and moderate by executive compensation. The theories that are related to this study are agency theory and bonus plan hypothesis. This study is a quantitative research that used secondary data of manufacturing companies listed on the Indonesia Stock Exchange from the period 2016 - 2019. The sampling technique is done by purposive sampling which results 58 companies with 232 data observations. The statistical analysis tool of this study is Smart-PLS version 3.3.2 to test the hypothesis. The results showed that tax avoidance has a negative significant influence on firm value, executive compensation has positive significant influence on firm value, and executive compensation moderate the relationship between tax avoidance and firm value.